Harder Than You Think – Immigrant Labor Market Integration in Agricultural Sector - Barth, Henrik; Zalkat, Ghazal (Nordic Journal of Working Life Studies, 2022)
The recent forced migration to Europe has created more challenges for the labor market integration. However, the Swedish government encourages unemployed immigrants to seek employment in the farming, gardening, and forestry industries. Thus, this article focuses on the matching process in the Swedish agricultural sector by using an exploratory, qualitative, in-depth interview with representatives involved in the matching process. Immigrants experience challenges of Swedish language proficiency, lacking a driving license and adapting to new cultures in the workplace, while employers attribute challenges of effective hiring process and the absence of evidence of immigrants’ work experience. Furthermore, the employment service offices struggle with scant knowledge of agricultural employment that needs to be combined with limited contact with employers and the bureaucratic delays caused by requirements of qualifications validation. The paper concludes with a Labour Market Matching Model, which focuses on critical aspects before, during, and after the matching process.